Pelatihan Keterampilan Teknik Dasar Permainan Bulu Tangkis di Desa Pandan Wangi Kabupaten Lombok Timur - Azis, Abdul (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
Badminton is a sport that is the pride of the Indonesian nation. Almost every region has the facilities and infrastructure to do this sport. The popularity of badminton has resulted in badminton players being able to compete at the international level. This should be maintained and developed in order to make the nation proud. There are five categories of badminton played, including men's singles, women's singles, men's doubles, women's doubles and mixed doubles. The game of badminton can not only be played on an open court (outdoor), but can also be played on a closed court (indoor). The shape of a badminton court is rectangular and there is a net in the middle that divides the area between two players or pairs. The aim of this activity is to train basic technical skills for playing badminton in Pandan Wangi Village, Jerowaru District, East Lombok Regency. The results achieved in training on basic techniques for playing badminton in Pandan Wangi Village within ± one and a half months include: 1) children know what the basic techniques for playing badminton are; 2) children already understand how to perform the basic technical movements of playing badminton; 3) develop players' abilities in playing badminton; 4) improve children's ability to perform basic badminton techniques; 5) improve brain cognition; 6) strengthen the muscles and joints of the body; 7) prevent a number of diseases; 8) make children interested in sports from previously often playing online games; 9) develop the quality of children in Pandan Wangi Village in playing badminton; and 10) maintaining body health by exercising, especially playing badminton.